2020
DOI: 10.5293/ijfms.2020.13.1.103
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of the Air Injection Effect on the Vortex Structure and Pulsation Characteristics in the Francis Turbine

Abstract: The paper studies the pulsation characteristics of the flow when operating a medium-scale hydrodynamic test bench with a Francis turbine. The pressure fluctuations measurements and flow structure visualization were performed for all operation modes of the hydraulic unit. To control and suppress pulsations in the flow path, a series of experiments on air injection to the hydraulic unit were carried out. Comparison of pressure pulsations for single-phase and two-phase flow experimentation has shown that for mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The findings reported by Platonov et al [38] demonstrated a significant effect of air injection on the intensity of pressure fluctuations obtained when operating a mediumscale hydrodynamic test bench with a Francis turbine. It was found that when air was injected at operating conditions close to the optimal regimes, a substantial increase in pressure pulsations was observed, while when air was injected under conditions with the maximum pulsations, it could significantly reduce the surge.…”
Section: Air Addition 21 Experimental Workmentioning
confidence: 89%
“…The findings reported by Platonov et al [38] demonstrated a significant effect of air injection on the intensity of pressure fluctuations obtained when operating a mediumscale hydrodynamic test bench with a Francis turbine. It was found that when air was injected at operating conditions close to the optimal regimes, a substantial increase in pressure pulsations was observed, while when air was injected under conditions with the maximum pulsations, it could significantly reduce the surge.…”
Section: Air Addition 21 Experimental Workmentioning
confidence: 89%
“…Several studies have focused on suppressing the flow instabilities associated with the vortex rope in the DT of a Francis turbine. Platonov et al [7] conducted an experimental study on the impact of air injection on the vortex flow pattern and the pressure pulsation under maximum load conditions. The air was injected into the spiral casing of a Francis turbine model, and pressure pulsations were reduced by almost 50% due to the injection.…”
Section: Introductionmentioning
confidence: 99%